2022
DOI: 10.31557/apjcp.2022.23.2.451
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Pediatric Oncological Patients and Their Parents/Guardians about a Hospital Oral Health Program: A Qualitative Study Perception About an Oral Health Program

Abstract: Background:The oral healthcare offered to pediatric cancer patients at the hospital level must include educational and preventive strategies based on dialogical and welcoming professional attitudes. Therefore, the current study aimed to evaluate the perception of pediatric cancer patients and their parents/guardians about an educational and preventive oral healthcare program implemented in a reference hospital for cancer treatment. Methods: A qualitative follow-up investigation was conducted in which we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Most parents describe oral hygiene moments as stressful for their children and for themselves. In younger children, parents must perform oral care accompanied by play activities (eg storytelling, playing music, composing puzzles) and using fun instruments (Robertson et al, 2019;Sampaio et al, 2021). Children need parents to maintain oral hygiene and health because of their limited knowledge and abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Most parents describe oral hygiene moments as stressful for their children and for themselves. In younger children, parents must perform oral care accompanied by play activities (eg storytelling, playing music, composing puzzles) and using fun instruments (Robertson et al, 2019;Sampaio et al, 2021). Children need parents to maintain oral hygiene and health because of their limited knowledge and abilities.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the oral health education and preventive program (OHEPP) analyzed in our study can be found elsewhere. 15,20 The data were entered into Microsoft Excel spreadsheets and analyzed descriptively and inferentially. Mean MGI and VPI values as well as the frequency distribution and mean OAG scores for each of the eight assessment sites were compared at baseline and throughout the 10 weeks of follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the oral health education and preventive program (OHEPP) analyzed in our study can be found elsewhere 15,20 …”
Section: Methodsmentioning
confidence: 99%
“…Nos estudos da amostra, os pesquisadores apontaram que o tratamento oncológico em pacientes pediátricos pode ocasionar possíveis complicações e efeitos colaterais podendo ser na forma aguda ou crônica, uma vez que esta população está na fase de crescimento e desenvolvimento. Outro ponto de convergência entre os pesquisadores foi sobre a ocorrência de complicações bucais em crianças ser de três vezes maior que em adultos, devido à alta atividade celular mitótica (Damascena, et al, 2018;Garrocho-rangel, et al, 2018;Garrocho-rangel, et al, 2018;Ribeiro, et al, 2019;Afshar, et al, 2020;Sampaio, et al, 2022;Lima, et al, 2022).…”
Section: Fonte: Autoras (2022)unclassified
“…O tratamento antineoplásico pode induzir dano celular no epitélio, mucosa oral e estruturas glandulares prejudicando suas funções e, consequentemente, promovendo alterações, que se manifestam como complicação estomatológica nos pacientes (Welter, et al, 2019). Dentre as complicações orais, encontram-se a mucosite, a osteorradionecrose, infecções oportunistas como a candidíase, xerostomia, doenças periodontais, perda ou diminuição do paladar e trismo, que tornam-se muito comuns em pacientes submetidos a essas modalidades de tratamento as quais, são responsáveis por gerar um enorme desconforto ao paciente, principalmente ao tratar se de pacientes infantis (Lopes, et al,2012;Do Nascimento, et al, 2013;Azhe, et al,, 2013;Dholam, et al, 2014;Pinto, et al,, 2014;Rosso, et al,2015;Melo Júnior, et al,2016;Murshid, et al,2017;Ribeiro, et al, 2017;Costa, et al, 2018;Damascena, et al,2018;Garrocho-rangel, et al, 2018;Garrocho-rangel, et al, 2018;Ribeiro, et al, 2019;Afshar, et al, 2020;Ribeiro, et al, 2020;Damascena, et al, 2020;Velten, et al, 2017;Pinto, et al, 2018;Aggarwal & Keerthilatha, 2018;Welter, et al, 2019;Ali, 2019;De Oliveira Ponte, et al, 2019;Wang, et al, 2021;Guedes, et al, 2021;Sampaio, et al, 2022;Lima, et al, 2022).…”
Section: Fonte: Autoras (2022)unclassified